Consumer Acceptance of Eco-Friendly Products in Pakistan: A Qualitative Study Based on Consumer Behavior Theory - Fuzail, Muhammad (Aurora: Journal of Emerging Business Paradigms, 2025)
This study investigates the factors influencing consumer acceptance of eco-friendly products in Pakistan, using consumer behavior theory as a conceptual framework. By applying a qualitative research design, in-depth interviews were conducted with 18 participants to uncover the underlying psychological, social, and situational factors that drive or hinder sustainable consumption. The study finds that environmental awareness, attitudinal beliefs, and social norms significantly shape consumer intentions, while behavioral control barriers such as high product costs, limited accessibility, and inconvenience remain the primary inhibitors. Notably, social influence from reference groups, including family and peers, was identified as a powerful force, with younger, urban consumers showing greater eco-friendly preferences due to social pressure and media exposure. Perceived behavioral control—influenced by affordability, convenience, and availability—emerged as a critical determinant of consumer behavior. The findings reveal that while consumers express positive attitudes towards green products, practical challenges prevent the widespread adoption of eco-friendly alternatives. This research contributes to the literature by offering novel insights into the unique contextual factors influencing green consumer behavior in a developing country like Pakistan. It emphasizes the importance of tailored marketing strategies and policy interventions to address barriers and promote sustainable consumption. For marketers and policymakers, the study suggests that addressing cost concerns, improving product availability, and fostering trust in environmental claims can facilitate the adoption of eco-friendly products. Future research could explore the longitudinal impact of such interventions.